A dança do ventre na qualidade de vida de mulheres com transtornos de humor (depressão maior e bipolaridade) frequentadoras do CAPS II – Canoas - Alves, Cristina Maria Ruschel (2015)
This paper aims to understand how the danced movement in belly dancing by the CAPS II - Canoas women members promotes a process of emotional integration, social, bodily the individual and the improvement of quality of life. It consists in a qualitative research method with the design of action research. The collection technique used was participant observation, through alternative technique "belly dance workshops." The research tools were a field diary to record the actions, information, observations and impressions in belly dance workshops. The implementation of semi-open interviews recorded and transcribed, and the analysis categories consist of three dimensions: the physical body , conscious and social , that come together and form the body dancing. The results showed the Belly Dance as a positive therapeutic aid in the treatment , as a complementary therapy, helping them in the process of integration making them more secure and confident. The final product was a booklet indicating which methodology used in belly dance workshops for women with depression and bipolar users of CAPS II.